Sero-epidemiological prevalence of leptospirosis among animals in south Gujarat - Dipal Jethwa; Darshan Chauhan; Tanvi Panwala; Summaiya Mulla (Journal of Veterinary and Animal Sciences, 2025)
Leptospirosis is one of the neglected tropical diseases affecting humans, as well as wild and domestic animals. Livestock and pets also serve as asymptomatic reservoir hosts and can be a source of infection for humans in contact with them. While leptospirosis is usually mild and often subclinical in cattle, it can lead to higher incidences of abortion, stillbirth, infertility, mastitis, weak progeny, decreased milk production, and ultimately economic losses in livestock. The present study was conducted with the primary aim of assessing the seroprevalence of leptospirosis and identifying the prevalent leptospira serovars in cows, buffaloes, goats, and sheep in the South Gujarat districts. Serum samples obtained from different animals in the South Gujarat districts were tested for leptospirosis using Microscopic Agglutination Test (MAT) in the Microbiology Department of Government Medical College, Surat, Gujarat, India, from January 2021 to December 2023. The data were entered into Microsoft Excel, and OpenEpi software version 3.01 was used to calculate the chi square test and p-value to analyze the level of significance in the presence of Leptospira among different animals. Out of 2,845 serum samples tested, 358 (12.58) demonstrated the presence of agglutinating antibodies against leptospires by MAT test. Serovar-wise analysis showed that the predominant serovars in cattle were Hardjo (16.2), Icterohaemorrhagiae (15.7), Autumnalis (10.6), Hebdomadis (10.6), and Pomona, (10.6). In buffalo, the predominant serovars were Hardjo (24.6), Icterohaemorrhagiae (18.1), Pomona (13), Patoc (12.3), Batavia (8.7), and Hebdomadis (8). In goats, the predominant serovars were Autumnalis 26.6), Australis (13.3), Icterohaemorrhagiae (13.3), Patoc (11.1), Pomona (6.6), and Hebdomanis(6.6).Periodic surveillance for leptospirosis in animals plays a vital role in creating awareness among the people regarding the diseaseand assists the farmers and public health workers to devise various control strategies.